Fibroblast growth factor receptors, developmental corruption and malignant disease - Kelleher, F. C.; O'Sullivan, H.; Smyth, E.; McDermott, R.; Viterbo, A. (Carcinogenesis (New York), 2013)
Fibroblast growth factors (FGF) are a family of ligands that bind to four different types of cell surface receptor entitled, FGFR1, FGFR2, FGFR3 and FGFR4. These receptors differ in their ligand binding affinity and tissue distribution. The prototypical receptor structure is that of an extracellular region comprising three immunoglobulin (Ig)-like domains, a hydrophobic transmembrane segment and a split intracellular tyrosine kinase domain. Alternative gene splicing affecting the extracellular third Ig loop also creates different receptor isoforms entitled FGFRIIIb and FGFRIIIc. Somatic fibroblast growth factor receptor (FGFR) mutations are implicated in different types of cancer and germline FGFR mutations occur in developmental syndromes particularly those in which craniosynostosis is a feature. The mutations found in both conditions are often identical. Many somatic FGFR mutations in cancer are gain-of-function mutations of established preclinical oncogenic potential. Gene amplification can also occur with 19-22% of squamous cell lung cancers for example having amplification of FGFR1. Ontologic comparators can be informative such as aberrant spermatogenesis being implicated in both spermatocytic seminomas and Apert syndrome. The former arises from somatic FGFR3 mutations and Apert syndrome arises from germline FGFR2 mutations. Finally, therapeutics directed at inhibiting the FGF/FGFR interaction are a promising subject for clinical trials.